Idealitas Penguatan Kewenangan DPD RI dalam Perspektif Ketatanegaraan Indonesia yang Dinamis* - M Muslih (Universitas Batanghari Jambi, 2019)
The Regional Representative Council is a new institution that replaces the Group and Regional Representatives as well as functions as a legislative member. However, the existence of this DPD has not been used optimally and is not